Intrahospital Transport Practice in Pediatric Intensive Care Units - Mehmet Ünal; Perihan Aydın; Nazan Ülgen Tekerek; Oğuz Dursun; Erdem Çebişli; Alper Köker (Galenos Yayinevi, 2023)
Introduction:Critically ill children often require transport during diagnosis and treatment procedures during intensive care hospitalization. With this study, it was aimed to evaluate the practice of transport and the problems encountered during transport in pediatric intensive care units in Turkey.Methods:A questionnaire consisting of 18 questions was filled in with internet access by the head nurses of the pediatric intensive care unit, who agreed to participate in the study. Responses to questions about the characteristics of the participating centers, transport practices, problems encountered during transport, interventions and the registration system were evaluated.Results:A total of 29 tertiary pediatric intensive care units from 8 provinces in Turkey were included in the study. The mean number of beds was 14. In most pediatric intensive care units, 5 to 10 patients (51.7%) were transferred within 1 week. It was observed that the most patients were transported to the inpatient service (89.7%), followed by the operating room (69%). There was a protocol for patient transport in 69% of the units. The transport decision was made by the responsible specialist physician at a rate of 96.6%. 65% of the participants stated that the transport was recorded on a form. Transports were accompanied by 93% nurses, 86% allied health personnel, and 79% doctors. In 20 centers (69%), transport was possible with an invasive mechanical ventilator and 11 (37.9%) with a non-invasive mechanical ventilator. The most common problem encountered during transportation was the inadequacy of the physical conditions of the hospital (48.3%). There were 4 (13.8%) participants who encountered problems during patient transport in the last week. It was stated that the oxygen tube was depleted in one of them, and respiratory arrest developed in another patient.Conclusion:In this study, it was shown that; In our country, there are significant differences in intrahospital transport conditions, transport teams, equipment used during transport between centers. Transport standards should be established and these should take into account the conditions of our country. For these, compliance and monitoring mechanisms should be established.